Gertrude Quastler papers - Quastler, Gertrude, 1909-1963.
Correspondence, notes, price lists, photographs, and other papers relating to Quastler's career as an artist, exhibitions of her work, and her activities in arranging art shows at Brookhaven National Laboratory, Upton, N.Y. Correspondents include her husband, Henry Quastler, and artists Richard Diebenkorn and Balcomb Greene.
Artist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Diebenkorn, Richard, -- 1922-1993 -- Correspondence; Greene, Balcomb, -- 1904- -- Correspondence; Quastler, Henry -- Correspondence; Art -- Exhibitions; Art -- New York (State) -- Union -- Exhibitions; Women artists -- United States; Brookhaven National Laboratory; Artists